Diversifikasi Investasi Saham: Perbandingan Risiko Total Portofolio Melalui Diversifikasi Domestik Dan Internasional - Auruma S, Tyas; Sudana, I Made (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2016)
This study aims to obtain two empirical proofs, are about the difference of total portfolio risk between internationally diversification and domestically diversification, then, the influence of the number of shares in the portfolio toward the total risk of portfolio. The model analysis used in this study is the difference t test on average two independent sample groups and for effect estimation, using simple regression equation. There were 21 blue chips stocks( LQ45 Indonesia;DAX30 German;FTSE100 UK;DJA – USA) choosen randomly, and used as sampel for both of internationally diversification and domestically diversification within period beginning January until December 2011. The results show that there are a difference in the total risk of the portfolio which is generated through internationally diversification and domestically diversification .Total risk of portofolio internationally diversification is smaller than total risk of portfolio domestically diversification, and the number of shares in portfolio affect significant negative toward the total risk of portfolio.